Skills, Exports, and the Wages of Five Million Latin American Workers - Brambilla, Irene; Carneiro, Rafael Dix; Lederman, Daniel; Porto, Guido (2012)
The returns to schooling or the skill premium is a key parameter in various literatures, including globalization and inequality and international migration. This paper explores the skill premium and its link to exports in Latin America, thus linking the skill premium to the emerging literature on the structure of trade and development. Using data on employment and wages for over five million workers in sixteen Latin American economies, the authors estimate national and industry-specific skill premiums and study some of their determinants. The evidence suggests that both country and industry characteristics are important in explaining skill premiums. The analysis also suggests that the incidence of exports within industries, the average income per capita within countries, and the relative abundance of skilled workers are related to the underlying industry and country characteristics that explain skill premiums. In particular, higher sectoral exports are positively linked with the skill premium at the industry level, a result that supports recent trade models linking exports with wages and the demand for skills.